Emerging incidence of pod rot caused by Choanephora cucurbitarum (Berk. & Rav.) Thaxter in dolichos bean (Dolichos lablab L.) and its management in Odisha, India - Byripogu, Arun; Subrata , Sarkar; Anita , Mohanty; Pravasini, Behera; Samikshya , Sanklini Pradhan; Udayendu, Barik; Aurobinda , Behera; Kalyan , Kumar Mohanty; Disha , Baishnabi (Plant Science Today, 2026)
Dolichos bean (Dolichos lablab L.) is an important legume vegetable crop widely grown in India. The research farm of All India Coordinated Research Project (AICRP) on Vegetable Crops, Odisha University of Agriculture and Technology (OUAT), Bhubaneswar, Odisha, situated in Eastern India, first recorded the incidence of Choanephora blight during the months of August–October 2023–24. During the subsequent kharif season of 2023–24 a survey was conducted in key dolichos bean farming areas in Odisha, such as Khordha, Cuttuck and Ganjam. According to the results of the survey, which were collected from all areas, the disease incidence ranged from 17–33 %. Therefore, research into the etiology and thorough symptomatology was undertaken. Based on the morphological features, molecular characterisation and pathogenicity test, Choanephora cucurbitarum (Berk. & Rav.) Thaxter was identified as the causal agent of pod rot in dolichos bean. The in vitro evaluation of fungicides indicated potential for disease management. Specifically, hexaconazole 5 % Emulsifiable Concentrate (EC) and azoxystrobin 12.5 % + tebuconazole 12.5 % Suspension Concentrate (SC), were shown to be effective against the test pathogen.